Rhizobium leguminosarum exopolysaccharide mutants: biochemical and genetic analyses and symbiotic behavior on three hosts. - Diebold, R (1989)
Ten independently generated mutants of Rhizobium leguminosarum biovar phaseoli CFN42 isolated after Tn5 mutagenesis formed nonmucoid colonies on all agar media tested and lacked detectable production of the normal acidic exopolysaccharide in liquid culture. The mutants were classified into three groups. Three mutants harbored Tn5 insertions on a 3.6-kilobase-pair EcoRI fragment and were complemented to have normal exopolysaccharide production by cosmids that shared an EcoRI fragment of this size from the CFN42 genome. The Tn5 inserts of five other mutants appeared to be located on a second, slightly smaller EcoRI fragment. Attempts to complement mutants of this second group with cloned DNA were unsuccessful. The mutations of the other two mutants were located in apparently adjacent EcoRI fragments carried on two cosmids that complemented those two mutants. The latter two mutants also lacked O-antigen-containing lipopolysaccharides and induced underdeveloped nodules that lacked nitrogenase activity on bean plants. The other eight mutants had normal lipopolysaccharides and wild-type symbiotic proficiencies on bean plants. Mutants in each of these groups were mated with R. leguminosarum strains that nodulated peas (R. leguminosarum biovar viciae) or clovers (R. leguminosarum biovar trifolii). Transfer of the Tn5 mutations resulted in exopolysaccharide-deficient R. leguminosarum biovar viciae or R. leguminosarum biovar trifolii transconjugants that were symbiotically deficient in all cases. These results support earlier suggestions that successful symbiosis with peas or clovers requires that rhizobia be capable of acidic exopolysaccharide production, whereas symbiosis with beans does not have this requirement.